Unveiling the Pharmacological Potential of a Pyrazole-Benzodioxole Hybrid Computational Analysis, ADMET Screening, and Molecular Docking Against ABL Tyrosine Kinase - Yilmaz, Mucahit; Kebiroglu, Mehmet Hanifi (Wiley-V C H Verlag Gmbh, 2026)
In this study, the physicochemical, electronic, and interaction properties of a pyrazole-benzodioxole hybrid molecule, 3-(1,3-benzodioxol-5-yl)-1H-pyrazole-5-carboxylic acid (C11H8N2O4), were systematically investigated using integrated in silico approaches. The novelty of this work lies in combining density functional theory (DFT), noncovalent interaction analysis (NCI/RDG), electron localization function (ELF), thermochemical evaluation, multiplatform toxicity prediction, and molecular docking within a unified computational framework. The results indicate that weak noncovalent interactions play a key role in stabilizing molecular conformation, while thermodynamic behavior is primarily governed by vibrational contributions. Toxicity predictions suggest a mixed safety profile, including potential mutagenicity and developmental toxicity, highlighting important limitations. Molecular docking against ABL tyrosine kinase reveals a moderate binding affinity (-6.588 kcal/mol), which is lower than that typically reported for strong inhibitors, indicating that the compound does not exhibit high inhibitory potency. Overall, the findings suggest that the investigated molecule may serve as a preliminary scaffold for further structural optimization, and its pharmacological relevance requires comprehensive experimental validation.
Keywords: ABL tyrosine kinase; ADMET; NCI/RDG; toxicity